NORMA SOSIAL MASYARAKAT DESA NUSAPATI DALAM PENGELOLAAN HUTAN RAKYAT - Rahman, Erry; Roslinda, Emi; Kartikawati, Siti Masitoh (Universitas Tanjungpura, 2016)
The forest condition progressively reduced so that the desire to maintain a strong forest of the village community Nusapati. Social norms is one of the factors affection the forests, because social norms can prevent people to do the wrong behavior, such as deforestation the forestation. This study aimed to determain characteristics of a society consisting of age, education, ethnicity, land, occupation, gender and religion in community forest management and to determine whether social norms play an importan role in the management of community forests. This research was conducted in September 2015 located Nusapati village. The survey method with interview, sampling studies using total sampling and data collection techniques using primary and secondary data. The collected data are analyzed and presented descriptively. The research showed condocted on sosial norms, the comunity adhere to unwritten rules rather than written rules. Unwritten rules include tolak bala ritual andÂ deliheration to resolvethe problem in the management of public forest (hutan rakyat). Keywords: social norms, community forests, communities.